Latest Digital Marketing Strategies: Increasing Relevance and Engagement with Customers - Jusuf, Dewi Indriani (SEAN Institute, 2022)
This research aims to analyze the latest digital marketing strategies that can increase relevance and interaction between companies and customers. In an era of continuously developing technology, it is important for companies to adapt relevant and effective marketing strategies to maintain their competitiveness in an increasingly competitive market. Through a qualitative descriptive approach, this research analyzes the latest trends in digital marketing, focusing on aspects of content relevance and customer interaction. The research results show that there is an urgent need for companies to adopt more personalized and relevant digital marketing strategies, with a focus on using content tailored to consumer preferences and behavior. This research also identifies several key factors that influence interactions between companies and customers via digital platforms. Based on these results, it is recommended that companies consider a marketing approach that focuses on adequate user experience and ongoing interaction with customers.